Optimization of clamshell content for improved properties in bamboo-epoxy composites (Fracture and Structural Integrity, 2024)
The present study aims to develop a novel hybrid composite by incorporating clamshell as a secondary reinforcing filler into a bamboo-epoxy composite. The primary objective of this hybridization is to optimize the synergistic benefits of each component, harnessing the strength of bamboo fibres, the durability of epoxy, and the cost-effective repurposing of the waste clamshell. Compression moulding was employed to develop composites with varying filler content (0- 9 wt%). The effect of filler on the physical and mechanical properties of bamboo-epoxy composites was evaluated by conducting tests as per ASTM standards. Experimental results show that the addition of clamshell filler significantly improved composites' properties, but there was a limitation to the addition. Hardness, tensile, and flexural properties were increased, whereas impact strength was reduced. Composites with 6 wt% clamshell exhibited optimum properties, enhancing tensile strength by 20.5% and flexural strength by 24.4 % compared to composites without filler. SEM analysis of fractured tensile and bending specimens revealed an enhanced fibre-matrix bonding with the inclusion of filler and supported the experimental results obtained. The outcome of this study contributes to sustainable development by using natural resources like bamboo fibre and repurposing seashell waste to create cost-effective composite material with enhanced properties.
Keywords: Seashell waste, Clamshell, Bamboo fibre, Mechanical Properties